Criminal justice and taxation - Alldridge, Peter (Oxford : Oxford University Press, 2017)
This volume presents a topical and lively discussion of how the criminal justice system attempts to ensure compliance with tax responsibility. Alldridge highlights the development of tax evasion offences and the relationship between evasion and evidential rules, prosecution structures, and alternatives to prosecution.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 15, 2017).
Keywords: Tax evasion -- Great Britain; Law; Laws of specific jurisdictions & specific areas of law